Transformational Leadership, Organizational Culture and Engagement on Innovative Behavior : A Review - Nurul Azmi; Yunda Liana; Zulkifli Musannip Efendi Siregar (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
The purpose of this study was to examine the literature relating to the influence of transformational leadership, organizational culture and engagement on innovative behavior. A leader who is able to give his role well will be able to increase good organizational commitment, increase employee motivation and increase employee innovative work behavior. Many types of leadership have been suggested by experts, but in this study, the authors will focus on discussing transformational leadership in relation to employee innovative behavior. Transformational leadership will be able to move employees to work harder, be creative and innovative at work. The method in this study is a review article. Articles were selected as many as 25 articles. The results of the study show that transformational leadership, organizational culture, and engagement influence employees' innovative behavior at work. Keyword : Transformational Leadership, Organizational Culture, Engagement, Inovative Behavior